CONSIDERATIONS AND IMPLICATIONS OF INDIGENOUS EDUCATION POLICY IN ONTARIO:: AN ANALYSIS OF RHETORIC (Canadian Journal of Native Studies, 2026)
The Ontario Ministry of Education’s (OME) ImplementationPlan: Ontario First Nation, Métis, and Inuit Education PolicyFramework (2014) restates its commitment to the principles ofthe 2007 Policy Framework. This analysis examines the valueorientations and assumptions couched in the rhetoric of the2014 Implementation Plan. The paper first situates Indigenouseducation in a contemporary context, and subsequently discussesthe implications of the respective discourses as they areframed in the Implementation Plan document. The intent is toprovide Indigenous and non-Indigenous students, communities,Indigenous education councils, administrators, teachersand other stakeholders with critical considerations of the OMEIndigenous education policy initiatives.